Tingkat Literasi Digital Mahasiswa Teknik Informatika dan Ilmu Komunikasi Universitas Muhammadiyah Bengkulu: Tinjauan Berdasarkan Kompetensi Individu - Putri, Salsa Nabila; Kurniawati, Juliana (Jurnal Audiens, 2025)
This study examines the digital literacy of students at Universitas Muhammadiyah Bengkulu across three dimensions of individual competence: use skills, critical understanding, and communicative abilities. A mixed methods approach with a convergent parallel design was employed, integrating quantitative data from 74 respondents collected via a 5-point Likert scale questionnaire and analyzed using descriptive statistics and independent sample T-tests, along with qualitative data from in-depth interviews with 10 informants analyzed thematically. The findings indicate that students’ digital literacy ranges from sufficient to high, with differences across study programs. Informatics students excel in use skills, whereas Communication students demonstrate stronger critical understanding and communicative abilities. The T-tests revealed significant differences across all three dimensions: use skills (t = 2.150; p = 0.034), critical understanding (t = 1.993; p = 0.049), and communicative abilities (t = 1.993; p = 0.040). Qualitative findings reinforce the quantitative results, highlighting differences in patterns of media usage, comprehension, and practices according to academic orientation. The study underscores that digital literacy is shaped by a combination of individual competence and educational context. These findings are crucial for designing digital literacy programs tailored to the specific needs of different academic disciplines, enabling students to become critical, responsible, and adaptive digital users in the information age.